Design and implementation of an ultrasonic sensor for rapid monitoring of industrial malolactic fermentation of wines - (:unkn) unknown (TAYLOR & FRANCIS INC, 2018)
Ultrasound is an emerging technology that can be applied to monitor food processes. However, ultrasonic techniques are usually limited to research activities within a laboratory environment and they are not extensively used in industrial processes. The aim of this paper is to describe a novel ultrasonic sensor designed to monitor physical-chemical changes that occur in wines stored in industrial tanks. Essentially, the sensor consists of an ultrasonic transducer in contact with a buffer rod, mounted inside a stainless steel tube section. This structure allows the ultrasonic sensor to be directly installed in stainless steel tanks of an industrial plant. The operating principle of this design is based on the measurement of ultrasonic velocity of propagation. To test its proper operation, the sensor has been used to measure changes of concentration in aqueous samples and to monitor the progress of a malolactic fermentation of red wines in various commercial wineries. Results show the feasibility of using this sensor for monitoring malolactic fermentations in red wines placed in industrial tanks.
Keywords: Industrial measurements; malolactic fermentation; process monitoring; sensor design; ultrasound; FOOD; VELOCITY; VISCOSITY; MIXTURES; YEAST; TECHNOLOGY; BACTERIA; DENSITY; SYSTEMS; WAVES